The Importance of using Curriculum Projects in the Development of Students 'Personal and Creative Competence in the Field of Pedagogical Sciences - Turaboeva Madinahon Rakhmonjon qizi (International Journal on Integrated Education, 2021)
The article provides feedback and recommendations on the need to develop students' personal and creative abilities in the digital environment, opportunities for creative organization of pedagogical disciplines and the importance of using project assignments in the teaching of pedagogical disciplines to improve the quality of education.